PENGARUH INFORMASI AKUNTANSI TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Sarmila, Sarmila; Pawerangi, Syahrir; Musfira, Ria (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2024)
Research Objectives: To determine the influence of ROA, ROE, NPM and EBIT on share prices of manufacturing companies in the food and beverage sub-sector on the IDX simultaneously. To determine the influence of ROA, ROE, NPM and EBIT on share prices of manufacturing companies in the food and beverage sub-sector on the IDX simultaneously. Partial. This research uses a type of quantitative research from quantitative research to carry out measurements and assist in determining the relationship between variables in a population, including assisting in determining the research design. Research results 1. Based on the results of data analysis, the coefficient values for ROA, ROE, NPM and EBIT show an influence on stock prices simultaneously. 2. Based on the results of data analysis on ROA, ROE, NPM, they have a partially significant effect on share prices, while EBIT has no influence on the share prices of manufacturing companies in the food and beverage sub-sector on the IDX. 3. The variable that has the most dominant influence between ROA, ROE, NPM and EBIT on the share prices of manufacturing companies in the food and beverage sub-sector on the IDX is the ROA variable.